2009
DOI: 10.1016/j.neuropsychologia.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Change in background context disrupts performance on visual paired comparison following hippocampal damage

Abstract: (217 words; max=250)The medial temporal lobe plays a critical role in recognition memory but, within the medial temporal lobe, the precise neural structures underlying recognition memory remain equivocal. In this study, visual paired comparison (VPC) was used to investigate recognition memory in a human patient (YR), who had a discrete lesion of the hippocampus, and a group of monkeys with neonatal hippocampal lesions, which included the dentate gyrus, and a portion of parahippocampal region. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
2
32
1
Order By: Relevance
“…By contrast, it is impaired when familiarization is very brief, or when the familiar and novel items share overlapping features. This complements earlier reports of impaired VPC performance in monkeys with hippocampal lesions when novelty is limited to the spatial relationships between several items, or to the background of individual items (Bachevalier and Nemanic 2008;Pascalis et al 2009;J Bachevalier, S Nemanic, and M Alvarado, unpubl.). Thus, the hippocampus seems important for incidental recognition memory only when it relies on a fine-grained comparison of familiar and novel items (for similar data in rodents, see Wan et al 1999;Mumby et al 2002;Hoge and Kesner 2007;Hunsaker et al 2007;VanElzakker et al 2008).…”
Section: Role Of the Hippocampus In Memorysupporting
confidence: 88%
“…By contrast, it is impaired when familiarization is very brief, or when the familiar and novel items share overlapping features. This complements earlier reports of impaired VPC performance in monkeys with hippocampal lesions when novelty is limited to the spatial relationships between several items, or to the background of individual items (Bachevalier and Nemanic 2008;Pascalis et al 2009;J Bachevalier, S Nemanic, and M Alvarado, unpubl.). Thus, the hippocampus seems important for incidental recognition memory only when it relies on a fine-grained comparison of familiar and novel items (for similar data in rodents, see Wan et al 1999;Mumby et al 2002;Hoge and Kesner 2007;Hunsaker et al 2007;VanElzakker et al 2008).…”
Section: Role Of the Hippocampus In Memorysupporting
confidence: 88%
“…In the second block (the mixed block), some letters for the case decisions were presented in colour (red or blue), which turned them into bivalent stimuli. Our motivation for EPISODIC CONTEXT BINDING AND AMNESIA 6 involving amnesic patients was to test whether their profound deficit in memory binding, in particular binding an event to a particular context (e.g., Chun & Phelps, 1999;Hannula, Tranel, & Cohen, 2006;Pascalis, Hunkin, Bachevalier, & Mayes, 2009), would affect the bivalency effect. Several studies have demonstrated that the binding deficit in amnesia is not restricted to long-term memory, but also affects short-term bindings such as those thought to be involved in the bivalency effect (Olson, Moore, Stark, & Chaterjee, 2006;Ezzyat & Olson, 2008;Olson, Moses, Riggs, & Ryan, 2012 for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…These findings add to a body of evidence that the hippocampus is necessary when contextual information is important. We also confirm that memory deficits after chronic adrenalectomy are not a result of loss of corticosterone per se.Research with rats (Sutherland and McDonald 1990;Kim and Faneslow 1992;Anagnostaras et al 2001;Lehmann et al 2009), nonhuman primates (Machado and Bachevalier 2006;Pascalis et al 2009), and humans (Alvarez et al 2008;Marschner et al 2008) shows that hippocampal damage can disrupt the ability to recall or express information about context. Furthermore, several reports suggest that the hippocampus is important for creating flexible representations of context and object associations.…”
mentioning
confidence: 99%
“…Furthermore, several reports suggest that the hippocampus is important for creating flexible representations of context and object associations. Studies in rats (Mumby et al 2002;O'Brien et al 2006) and humans (Pascalis et al 2009) show that lesions specific to the hippocampus produce deficits in object recognition only when contextual information is altered.Within the hippocampus, the dentate gyrus (DG) is important for certain aspects of memory (Xavier et al 1999;Garthe et al 2009). Chronic adrenalectomy (ADX) causes a gradual and selective loss of granule cells in the DG of the rat (Sloviter et al 1989).…”
mentioning
confidence: 99%
See 1 more Smart Citation